2023
DOI: 10.1111/ejh.13956
|View full text |Cite
|
Sign up to set email alerts
|

Adverse impact of a high CD4/CD8 ratio in the allograft may be overcome by methotrexate‐ but not mycophenolate‐ or post‐transplant cyclophosphamide‐based graft versus host disease prophylaxis

Abstract: Introduction: A high CD4/CD8 T cell ratio in hematopoietic stem cell transplant (HSCT) allografts was observed to predict graft-versus-host disease (GVHD) and nonrelapse mortality (NRM) but has not been comparatively examined in settings of various GVHD-prophylaxis regimens.Methods: This retrospective monocentric study included all consecutive HSCT performed with peripheral blood stem cells between January 2000 and June 2021.The impact of the graft CD4/CD8 ratio was analyzed in three cohorts with different GVH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
2
1
Order By: Relevance
“…10 A high CD4/CD8 ratio (> 2.42) was associated with overall mortality (hazard ratio [HR], 2.07; P = 0.04) in HLA-mismatched HSCT with PTCybased GVHD prophylaxis. 9 Graft CD8 + T cells were not an independent factor in the development of GVHD in this study. In line with our findings, several studies have shown that the dose of CD8 + T cells in grafts has no impact on the GVHD.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…10 A high CD4/CD8 ratio (> 2.42) was associated with overall mortality (hazard ratio [HR], 2.07; P = 0.04) in HLA-mismatched HSCT with PTCybased GVHD prophylaxis. 9 Graft CD8 + T cells were not an independent factor in the development of GVHD in this study. In line with our findings, several studies have shown that the dose of CD8 + T cells in grafts has no impact on the GVHD.…”
Section: Discussioncontrasting
confidence: 45%
“…7,8 The cellular composition of grafts other than CD34 + cells also affects HSCT clinical outcomes. [9][10][11] However, different cellular populations in the grafts result in distinct clinical outcomes after HSCT. A higher dose of CD3 + T cells in the peripheral blood grafts of haploidentical HSCT (haplo-HSCT) reportedly increases the risk of acute graft-versushost disease (GVHD).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation